Monitoring the flow rate of water in the supercritical convection loop - Bakai, A.S.; Biller, E.Z.; Bovda, A.M.; Boriskin, V.N.; Gorenko, Yu.V.; Momot, V.A.; Onischenko, L.V.; Solodovnikov, V.I.; Shelepko, S.V. (Вопросы атомной науки и техники, 2016)
The Supercritical Water Convection Loop with an irradiation chamber is created in KIPT. The Loop is made from stainless steel. It measures 1.2 by 1.5 m. The plant makes possible to carry out simulation corrosion tests of potential structural materials for Generation IV reactors with the Supercritical Water-Cooling (SCWR) under irradiation. Specimens in water flow at 350…400°C, 23…25 MPa are irradiated by the 10 MeV/10 kW electron beam of LUE-10 linear accelerator. The monitor with powerful permanent magnets in the turning components is being devised for expeditious control of the flow water velocity.